Tinjauan Konsep Kota Pintar Surakarta: Optimalisasi Transformasi dan Layanan Digital Berbasis Big Data dan Teknologi Real-Time - Muhammad Ridwan; Zabilla Tomy Sanjaya; Thalita Aldila Pramitasari; Prabang Setyono (Research and Development Agency Ministry of Home Affairs, 2025)
Digital transformation and public facilities in city governance have become basic needs amidst the increasing complexity of public services and public demands for fast, transparent, and affordable services. Surakarta City, as a cultural city in the process of becoming a smart city, faces challenges in streamlining bureaucracy, improving residents' quality of life, and optimizing the use of real-time data. This study aims to identify and formulate a strategy for the Surakarta Smart City concept that focuses on the dimensions of smart governance, smart living, and smart society. The approach used integrates big data-based information technology and real-time technology. The research method uses literature studies from Scopus, Google Scholar, and Sinta. The research result showed that the current digital transformation in Surakarta has not optimally improved public services or access to information, nor has it accelerated responses to field conditions. The researchers recommend developing an integrative dashboard across sectors. Concretely, the smart city concept in Surakarta can be strengthened by: (1) the concept of adding public facilities such as the provision of public Wi-Fi in strategic city spaces, (2) optimizing the development of digital health services, (3) developing online-based population administration that can be accessed in real-time and responsively, and (4) implementing a real-time city monitoring system through the integration of CCTV and big data. These initiatives are considered capable of improving accessibility and quality of life and accelerating data-based decision-making. This research confirms that the success of a Smart City rests not only on technology, but also on collaborative governance, adaptive regulations, and community social readiness. Surakarta has great potential to become a model for a smart city based on culture and sustainable citizen participation.